Jazz Dance in menopause: protocol study for a randomized clinical trial Danza Jazz en la menopausia: estudio de protocolo para un ensayo clínico aleatorizado - Martins J.B.B.* (2024)
© 2024 Federacion Espanola de Docentes de Educacion Fisica. All rights reserved.Background: Dance as an example of Physical Activity, although not much studied, is shown as a positive non-pharmacological therapy that decreases physical, psychological, and sexual symptoms arisen from menopause. Objective: To provide a Jazz Dance protocol (twice a week / 12 weeks) for menopausal women and compare its effectiveness with the Control Group. Method: This study is a protocol for a randomized clinical trial with menopausal women with two arms: Control Group and Jazz Intervention Group. A 12-week protocol developed for women between the ages of 40 and 59 to analyze the Jazz Dance effect on the primary outcome: Menopause Symptoms (Menopause Rating Scale); and on the secondary outcomes - physical aspects: BMI, body fat percentage (Ultrasound (BX-2000, IntelaMetrix Inc., USA) alongside to Jackson & Pollock's 7 folds equation); fitness cardiorespiratory: (Treadmill (Embramed atl 2000) to lead the submaximal exercise test following the modified Bruce protocol); hormonal aspects: Follicle-stimulating hormone levels (blood sample), and psychological aspects- depressive symptoms and anxiety (Hospital Anxiety and Depression Scale); mood (Brunel Mood Scale) and stress levels (Perceived Stress Scale). Discussion: This study will be the first Jazz Dance protocol offered to support a new randomized clinical trial with menopausal women focused on dancing as a non-medicated treatment.